(untitled) (Biological Sciences - PJSIR, 2022)
Investigations were conducted to relate seed exudates conductance to standard germination so as to develop a quick and reliable test for measurement of cotton seed quality. Results showed thatcott. \11 cultiv ars differed significantly in germination percentage and electrical conductivity. Cultivars MNH-93 and C!ivt-l09 had higher germination percentage and less exudate conductance compared to othcr cultivars. Seeds obtained from first pick were of poor quality than those of second pick. The exudate conductance was negatively correlated with germination (r = - 0.88**). The loss of membrane functional integrity sel IIISresponsible lor lower germination. These data indicate that electrical conductivity test can provide estimates of seed quality,